(untitled) (Texas Journal of Philology, Culture and History, 2024)
This article reflects on the possibilities of designing lessons aimed at organizing a critical assessment of the personality of the heroes of a work,in addition to the formation of students ’ critical thinking and the development of konikmas of critical assessment of the heroes of the work,the analysis and translation of artistic texts, as well as many positive qualities.